Experimental Analysis on Double Layer Kapton Material using Peltier Thermoelectric Device - Dahalan, AH; Aziz, M.Z.A. Abd.; Othman, M.A. (IAES Indonesian Section, 2020)
Kapton is one of the flexible materials used in the development of microwave components for the telecommunications system. The electrical properties of Kapton are dependent on the material's temperature. In this study, this material will be heated, and the electrical properties of dielectric permittivity and loss tangent will be analyzed. This material heating process is done by using Peltier thermoelectric which is installed with Aluminium alloy. The 0 V up to 7 V DC voltage was supplied to the Peltier during the heating process. Then, the electrical properties of Kapton were measured by using a dielectric probe and vector network analyzer (VNA) at frequencies of 1 GHz to 9 GHz. The results obtained show the Kapton temperature was increased from 27oC to 41oC. Meanwhile, the dielectric permittivity also varied from 1.72 to 1.64 at the frequency of 5 GHz when 4 V was used. The maximum loss tangent value of 0.5 was observed when the maximum DC voltage of 7 V was applied. The knowledge of this experimental work can be used to design reconfigurable microwave components for smart system applications